2010
DOI: 10.1177/0192513x10363985
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Versus Fathers’ Alcohol Abuse and Attachment in Adult Daughters of Alcoholics

Abstract: Gender of the alcohol-abusing parent was examined in relation to general and romantic attachment (as measured by the Experiences in Close Relationships-Revised and the Relationship Scales Questionnaire) in female adult children of alcoholics (ACOAs; as indicated by the Children of Alcoholics Screening Test) as compared to non-ACOAs. As compared to non-ACOAs, ACOAs reported more anxious and avoidant behaviors in their romantic relationships. Female participants who suspected their mother of alcohol abuse report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
(45 reference statements)
0
5
0
2
Order By: Relevance
“…Kelley et al obtained similar results regarding insecure attachment styles by comparing women from the general population with women with ACoA syndrome who had co-dependent mothers. These women had dysfunctional attachment styles, especially high levels of attachment avoidance and anxiety [27].…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelley et al obtained similar results regarding insecure attachment styles by comparing women from the general population with women with ACoA syndrome who had co-dependent mothers. These women had dysfunctional attachment styles, especially high levels of attachment avoidance and anxiety [27].…”
Section: ■ Discussionmentioning
confidence: 99%
“…Podobny wynik dotyczący pozabezpiecznych stylów przywiązania otrzymali Kelley i wsp., porównując kobiety z populacji ogólnej z kobietami z syndromem DDA, które miały współuzależnione matki. Te drugie cechowały dysfunkcyjne style przywiązania, szczególnie wysoki poziom unikania i niepokoju przywiązaniowego [27].…”
Section: ■ Omówienieunclassified
“…They also reported high construct validity for the four-style model of adult attachment style measured in the model. However, several studies have reported variable internal consistencies for the RSQ subscales, ranging from alphas of .36 to .75 (Griffi n & Bartholomew, 1994;Kelley et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Baðlanma kuramýna göre, aileleriyle erken yaþantýlarýnda olumsuz yaþantýlarý sonucunda güvensiz baðlanma stili geliþtiren bireyler, sadece yakýn iliþkilerde deðil ayný zamanda stres altýnda iþlevsel olmayan tepkiler göstererek psikopatolojiye yatkýnlýk göstermektedirler (18). Bu baðlamda baðlanma stilleri ile klinik depresyon, panik bozukluk ve obsesif kompulsif bozukluk (19,20) gibi psikopatolojilerin yanýnda madde kullanýmý ile de arasýnda iliþkinin irdelendiði araþtýrmalar bulunmaktadýr (21,22,23,24). Yapýlan çalýþmalar dikkate alýndýðýnda madde kullanýmý ile genellikle güvensiz baðlanma stilinin iliþkili olduðunu ve bu bireylerde problemli madde kullanýmýnýn da anlamlý derecede yüksek olduðunu vurgulamaktadýr (21,23,43).…”
Section: Gýrýþunclassified